The structure of C290A:C393A Aurora A provides structural insights into kinase regulation - Burgess, Selena G. (Acta Crystallogr F Struct Biol Commun, 2015)
Aurora A is a Ser/Thr protein kinase that functions in cell-cycle regulation and is implicated in cancer development. During mitosis, Aurora A is activated by autophosphorylation on its activation loop at Thr288. The Aurora A catalytic domain (amino acids 122–403) expressed in Escherichia coli autophosphorylates on two activation-loop threonine residues (Thr288 and Thr287), whereas a C290A,C393A double point mutant of the Aurora A catalytic domain autophosphorylates only on Thr288. The structure of the complex of this mutant with ADP and magnesium was determined to 2.1 Å resolution using molecular replacement. This is an improvement on the existing 2.75 Å resolution structure of the equivalent wild-type complex. The structure confirms that single phosphorylation of the activation loop on Thr288 is insufficient to stabilize a ‘fully active’ conformation of the activation loop in the absence of binding to TPX2.